The parole supervision duties and the impediments under the prison legislation in Malaysia and New South Wales, Australia / Rafizah Abu Hassan - Abu Hassan, Rafizah (Institute of Graduate Studies, UiTM, 2018)
The parole system is responsible for rehabilitating prisoners and assisting them in their reintegration into the society successfully. Such a system aims at protecting public safety and reducing recidivism amongst the prisoners released on parole. Parole supervision involves the rehabilitation and surveillance duties of the parole officers. They must be able to balance these two competing duties in order to ensure the successful reintegration of the prisoners into the society, to prevent recidivism amongst them and to ensure community's safety. However, this dual role has not been adequately addressed by the current law under the Prison Act 1995. Therefore, the inadequacy of the Prison Act 1995 in providing the parole officers duties has led to the emergence of various challenges and impediments including legal, operational and technical concerns in performing their dual roles. Guided by this thesis, this study aims at examining the duties and impediments faced by the parole officers in their supervisory roles in Malaysia and the New South Wales, Australia with a view in eliciting lessons to be learned. Further, this research seeks to propose the strengthening of the existing law in assisting the parole officers. Finally, at the theoretical level, this research analysed how the Foucault disciplinary theory, the rehabilitation theory and the Klockars (MS) = Main Supervisor (CS) = Co Supervisor theory could benefit the parole officers in their parole supervision. This paper adopts a qualitative method, in which the primary data is obtained from five case studies of regional prisons which had established the parole system. Such data is triangulated with those from the Parole Board. The secondary data is obtained from the library-based approach. The evidence of this research is reported in Chapter Five. The legal analysis of the parole supervision in both jurisdictions is presented in Chapters Three and Four respectively. The findings suggest the absence of explicit provisions under the Prison Act 1995 in relation to the parole officers' rehabilitation and surveillance duties. This results with the parole officers being dominant in their surveillance duties although they were aware of their responsibilities in the rehabilitation of the prisoners. This study hopes to contribute in setting forward the recommendations to improve the Prison Act 1995 in empowering the parole officers with explicit parole supervision duties apart from contributing to the literature and enhance the legal knowledge of the parole system.